(untitled) (International relations and international law Journal, 2016)
Caspian region is a strategically very important space in term of energy geopolitics. In this paper we tried to study Energy Policies of Turkey in the Caspian Region and Central Asia. Turkey is a rather serious regional player which could balance the energy policies of Russia in Central Asia and compete with Iran in regional geopolitics. Turkey as a quickly growing economic power has complex strategy in diversification of energy deliveries from the different basins: Caspian region, Central Asia and Middle East. The policy of Turkey is explained by its comfortable geographic location which gives it an opportunity of being a corridor, transit-country and bridge between energy suppliers and customers. In this sense, Caspian Region and Central Asia becomes geo-strategically important region for Turkey.